Faktor-faktor Yang Berhubungan Dengan Pemberian Imunisasi Dasar Lengkap Pada Balita Di Wilayah Kerja Puskesmas Mutiara Barat Kecamatan Mutiara Kabupaten Pidie - Maijora, Cut Tiara; Aramico, Basri; Hasnur, Hanifah (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2023)
Immunization is one of the essential public health efforts that is effective in providing specific immunity against diseases that can be prevented by immunization. Mothers have a very important role in providing immunizations to children. The aim of this research is to determine the factors related to Complete Basic Immunization Coverage for Toddlers in the Working Area of Mutiara Barat Health Center, Pidie Regency in 2023. Method: this research is descriptive analytical with a cross-sectional approach. The population in this study was mothers who had toddlers aged (12-23 months). The sample was taken as many as 67 respondents using proportional random sampling technique. Data collection was carried out on January 16-26 2023 by means of interviews using a questionnaire. Data were analyzed univariately and bivariately using the chi-square test via SPSS. Results: univariate analysis showed that 92.5% of immunizations were incomplete, 56.7% knowledge was poor, 50.7% had side effects, 46.3% families did not support, 50.7% the role of health workers was poor, 41 .8% access to health facilities is unaffordable. Bivariate analysis showed that there was a relationship between knowledge (p-value 0.008), side effects (p-value=0.018), family support (p-value=0.031), role of health workers (p-value=0.018) and provision of complete basic immunization. Conclusion: Knowledge, side effects, family support, the role of health workers are related to immunization. It is recommended that community health centers provide more health program guidance and training to health workers to increase housewives' knowledge about the importance of complete basic immunization for toddlers.